Manifestações da violência nas relações conjugais no Maranhão republicano (1890-1920): dissoluções dos laços matrimoniais motivados pelo adultério e pela violência de gênero - SILVA, Douruézia Fonseca da (2012)
This paper presents an analysis of the manifestations of violence in marital relations, motivated by abuse, adultery, jealousy and extreme passion and, in some cases, allegations of conflict have reportedly been considered frivolous. For this, we used the theoretical studies on the theme of gender as a category of analysis in an attempt to establish a relationship with the cases in which conflicts came to a limit situation, triggering in criminal proceedings, crime or dissolution of marriage.Also this work were guiding to the Penal Civil Codes of 1890 and 1916, while support necessary to underpin the penalties resulting from conflicts in marital relationships / love.So, we sought to understand until the point of these new laws influenced the behavior of 'citizens' who lived in the context of the Republic. Then, we used the speeches of persons involved in situations of violence, either as defendant or as a victim.The intelligibility was always present in gender relations as well as the social practices of domination, especially in relationships, even having gone through these constant changes, because the power is a two-way street.